Agent-oriented ontology pattern classification for ontology-based multi-agent system development - Fu, Swee Tee. (Universiti Malaysia Sarawak (UNIMAS), 2012)
Multi -agent system have received much attention nowadays in various domains to solve complex problems within the open or closed enviroment. Ontology plays a crucial role within the multi-agent system in which it represents the information domain of the agent system. Furthermore, ontology is needed to govern agent interaction and agent behaviour. Work has been done to integrate ontology engineering approach within the MaSE methodology to include the use of ontologies for information domain specification. However,efficient developments of ontology are still a challenge as it requires extensive knowledge and experience for the underlying domain of interest. Therefore, with the issues faced above, there are still insufficient works to support the developments of ontology-based multi-agent system systematically.